Higher physical activity level and perceived social support is associated with less psychological distress in people with anxiety - Pereira Payo, Damián.; Denche Zamorano, Ángel.; Mayordomo Pinilla, Noelia.; Franco García, Juan Manuel.; Castillo Paredes, Antonio Jonathan.; García Gordillo, Miguel Ángel.; Rojo Ramos, Jorge.; Barrios Fernández, Sabina. (PeerJ Inc., 2023)
Introduction. Anxiety is one of the most prevalent mental illnesses in first world societies, generating discomfort in the people who suffer from it, and high expenses and economic losses in the society. The physical activity (PA) performed, together with the perceived social support (PSS) by people with anxiety could be related to the psychological distress of people with anxiety. Objectives. To study the relationships between mental health and its dimensions, through Golberg’s General Health Questionnaire (GHQ12), and the level of PA (PAL) and the PSS in the Spanish adult population with anxiety. Hypothesis. A higher PAL, and a higher PSS, is related to a lower psychological distress in this population. Design and Methodology. This study included 1,661 adults with anxiety, residents in Spain. It was a cross-sectional study with data obtained from the Spanish National Health Survey. A Kolmogorov–Smirnov test was applied to examine the data distribution of the variables. The median and interquartile range were used to characterize the sample for continuous variables, and absolute and relative frequencies were used for categorical variables. The Mann–Whitney U test was used to examine the differences between sexes. Dependence between PAL and sex was studied using the chi-square statistic. A Krustal–Wallis test was used to evaluate the existence of differences in the baseline medians on the GHQ-12, according to PAL level. Finally, the correlations between mental health and its dimensions with PAL and the Duke-UNC-11 scores were analysed, obtaining Spearman’s rho and Pearson’s correlation coefficient. Results. Moderate inverse correlations were found between the GHQ-12 and: PAL (rho: −0.219); PSS (r: −0.347). PAL and PSS presented moderate inverse correlations with successful coping (rho: −0.206 and r: −0.325), self-esteem (rho: −0.222 and r: −0.333) and stress (rho: −0.158 and r: −0.288). Conclusions. Greater PAL and social support are associated with reduced psychological distress in people with anxiety
Keywords: Kinesiología; Psiquiatría; Psicología; Salud pública; Salud mental